Space charge-induced unusually-high mobility of a solution-processed indium oxide thin film transistor with an ethylene glycol incorporated aluminum oxide gate dielectric. Issue 124 (30th November 2015) - Park, Hyungjin; Nam, Yunyong; Jin, Jungho; Bae, Byeong-Soo
Abstract : Undecomposed ethylene glycol residuals in solution processed aluminum oxide gate dielectric result in the frequency-dependent capacitance. Abstract : The incorporation of ethylene glycol (EG) into a high- k aluminium oxide gate dielectric layer was achieved by a solution process, leading to a distinct increase in the mobility of indium oxide TFT. Frequency-dependent capacitance originating from residual EG was examined and the accompanying effects on indium oxide TFT were studied.